ANALISIS PENGARUH TINGKAT PENGANGGURAN TERBUKA, TINGKAT PARTISIPASI ANGKATAN KERJA, UPAH MINIMUM, INDEKS PEMBANGUNAN MANUSIA, PERTUMBUHAN EKONOMI DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI KAWASAN TAPAL KUDA - Ashari, Rafi Taufik; Athoillah, Mohammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
East Java Province is one of the areas with a high poverty rate (Giovanni, 2018). East Java BPS (2019) explains that East Java ranks first with the largest number of poor people in Indonesia, where in 2019 it touched 4.05 million people with the greatest poverty occupied by districts in the Horseshoe region. This high poverty rate places the problem of poverty as one of the priorities in every development. Therefore, it is necessary to measure the factors that influence poverty in the Horseshoe region. This research is a descriptive study using a quantitative approach. The data used is secondary data. The analysis used in this research is panel data regression analysis to measure the significance of the variable effect of Open Unemployment Rate, Labor Force Participation Rate, Minimum Wage, Human Development Index, Economic Growth and Population on Poverty in the Horseshoe Region. The results of the study reveal that the Open Unemployment Rate, Labor Force Participation Rate, Minimum Wage, HDI, Economic Growth and Population simultaneously have a significant effect on poverty in the Horseshoe Region. The Open Unemployment Rate significantly adds to the number of poverty in the Horseshoe Region. The decline in labor force participation adds to the amount of poverty in the Horseshoe Region. The Minimum Wage adds to the poverty rate in the Horseshoe Region. The decline in HDI adds to the amount of poverty in the Horseshoe Region. Increased economic growth adds to the amount of poverty in the Horseshoe Region. The increase in population adds to the amount of poverty in the Horseshoe Region.